Affective partisan polarization and citizens' attitudes and behavior in Swiss democracy - Benjamin Jansen; Alois Stutzer (University of Basel, Center of Business and Economics (WWZ), 2024)
There is a concern that citizens with different political positions and party affiliations increasingly dislike each other. We examine this affective polarization (AP), which is often associated with a weakening of democracy, in the context of Switzerland's multiparty landscape with proportional governmental representation. Evaluating the long-term development of AP in Switzerland with both historical and newly gathered data for 2023, we find hardly any considerable change in AP over the last three decades, except for a substantial jump between 1999 and 2003 and a generally lower level of party sympathy in 2023. Complementary, our analysis of split-ticket voting behavior in national parliamentary elections with continuous data back to 1983 does not support any trend in partisan polarization from a voters' revealed preference perspective. We further find that more affectively polarized individuals report, on average, lower satisfaction with democracy but show a higher willingness to participate in politics across a wide range of different forms of political engagement, even when controlling for individuals' general sympathy towards political parties.
Keywords: D72; D91; 330; affective polarization; political participation; political discussion; latent candidacy; splitticket voting